Artemether-lumefantrine exposure in HIV-infected Nigerian subjects on nevirapine-containing antiretroviral therapy. - Parikh, Sunil; Fehintola, Fatai; Huang, Liusheng; Olson, Alexander; Adedeji, Waheed A; Darin, Kristin M; Morse, Gene D; Murphy, Robert L; Taiwo, Babafemi O; Akinyinka, Olusegun O; Adewole, Isaac F; Aweeka, Francesca T; et al. (Antimicrobial agents and chemotherapy, 2015)
Co-administration of nevirapine-based antiretroviral therapy (ART) and artemether-lumefantrine is reported to result in variable changes in lumefantrine exposure. We conducted an intensive pharmacokinetic study in 11 HIV-infected adults receiving artemether-lumefantrine plus nevirapine-based ART and compared results to 16 historical HIV-negative adult controls. Exposure to artemether and lumefantrine was significantly lower, while dihydroartemisinin exposure was unchanged in subjects receiving nevirapine-based ART compared to controls. Nevirapine exposure was unchanged before and after artemether-lumefantrine.